The secret Saturdays. Volume 1 - Stephens, Jay, 1971-; Jeralds, Scott; Lerner, Sam, 1993-; Morris, Phil, 1959-; Sullivan, Nicole, 1970-; Bader, Diedrich, 1966-; Cartoon Network (Television network); PorchLight Entertainment (Firm); Warner Home Video (Firm) (Burbank, CA : Distributed by Warner Home Video, 2009)
Follows the Saturday clan of scientists, out to protect the world from the strange monsters of the underworld.
The Kur stone. Part 1 -- The Kur stone. Part 2 -- The vengeance of Hibagon -- The ice caverns of Ellef Ringnes - - Guess who's going to be dinner.
Title from disc label and main menu.
Features: drawings, Cryptid catalog, deleted scenes.
Voices: Sam Lerner, Phil Morris, Nicole Sullivan, Diedrich Bader.
Originally broadcast on television in 2008.
TV rating: TV-Y7; FV.
DVD; Dolby Digital stereo 2.0.
Keywords: Cryptozoology -- Juvenile films; Monsters -- Juvenile films; Families -- Juvenile films; Video recordings for the hearing impaired; Monsters -- Drama; Families -- Drama; Animated television programs; Children's television programs; Science fiction television programs; Action and adventure television programs; Fiction television programs; Animated television programs; Science fiction television programs; Action and adventure television programs; DVD-Video discs